Soft Soil Retrofitting Study with Bamboo Concave Mattress Against Stability of Jombang - Kertosono Railway Double Track Slope Due to Earthquake Load - Suprayitno Suprayitno; Helmy Darjanto (LPPM NAROTAMA UNIVERSITY, Indonesia, 2018)
Soft soil in construction work is a problem. This is due to the low carrying capacity of the land. Low carrying capacity can cause losses, ranging from losses in terms of construction costs that are increasingly expensive, to the threat of construction safety, ie structures that are made unable to stand stably. The stability of the soft soil found in the location of the railway double track planning can be improved by the method of bamboo slab mattress because the carrying capacity of the soil increases due to pressure from the bamboo slabs that enter the soil. In this study bamboo slabs were used in order to strengthen the stability of embankments on the double track railroad where the embankment did not experience the collapse of the load of the pile itself or due to the burden of the passing train. The earthquake load can affect the stability of the slope of the double track railroad, this is evidenced from the analysis using the plaids program so that the internal force can be known. In the writing of this study, we will draw a picture of soft soil reinforcement modeling with bamboo slabs, which analyzes the calculations with additional earthquake loads. This can be a reference in the implementation of the construction of railroad lines in Indonesia, which are located in vulnerable locations with wetland conditions or rice fields